Refractive Temperature - Court, Arnold (The International Hydrographic Review, 2018)
Refraction tables used in navigation and surveying are almost cl I derived from those of Bessel, whose computations, based on English star observations, assume that atmospheric temperature decreases with height at the rate of about 0.6 F.° per 1,000 ft. Neither this assumption nor that of any subsequent investigator is entirely in accord with present-day knowledge of atmospheric structure, which generally has a temperature decrease of around 3 F.° per 1,000 ft. to the tropopause, with widely varying conditions above it. The Bessel tables in general use cannot be extrapolated for surface air temperatures much different from -0° F . ; in particular, for extreme cold conditions it is desirable to use, in place of the actual air temperature, the refractive temperature, which is that temperature for which the refraction correction given in the tables equals the correction which is actually required, and which may be estimated from general climatic considerations.